Sexual desire, sexual functioning and well-being in married males: a community based study - G. Lakshmana; F. Mohd; A. B. Panda (Sri Lanka Journal of Psychiatry, 2020)
Background Sexual dysfunction is a common yet treatable condition, which is associated with significant negative effects on the quality of life. However the true nature of this problem in India is not known, as many people are hesitant to discuss this topic.   Aims The study aimed to measure sexual desire, sexual functioning and well-being among married men in a regional city in India.   Methods Fifty-four males were recruited using cluster sampling. Assessments were conducted using the sexual desire inventory, brief sexual functioning inventory and PGIgeneral well-being scales.   Results Of the participants, 98% had a moderate level of overall sexual desire, while 81% reported sexual dysfunction, 58% reported moderate problems in ejaculation and 50% reported moderate problems in erection. A majority (85%), reported good general well-being. Age was negatively correlated with sexual functioning and sexual desire, whereas general wellbeing showed a positive correlation.   Conclusions Sexual dysfunction is a common problem in Indian males. Increase in awareness about these problems may encourage people to seek treatment for these important health issues.